2018
DOI: 10.3390/rs10020234
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Tropospheric Tomography Method Based on the Multi-GNSS Observations

Abstract: Abstract:Aside from the well-known applications (positioning, navigation and timing) brought by Global Navigation Satellite System (GNSS), reconstruction of tropospheric atmosphere distribution information using tomography technique based on the multi-GNSS observations has been developed as a research point in the fields of GNSS Meteorology. In this paper, an optimal tropospheric tomography method using observations from multi-GNSS (Global Navigation Satellite System) is proposed, which considers the reasonabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The RS-WV shown in Figure 10a is more even than that in Figure 10b, which is near the ideal WV distribution in the vertical direction. Zhang et al [24] stated that the WV with an even distribution is beneficial for good tomography results obtained by the GNSS-WV tomography. Hence, at the epoch in Figure 10a, the WV profiles obtained by the two tomography methods were in good agreement with that obtained by the RS-Method.…”
Section: Tomography Results For the Comparison Between Methods 1 Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The RS-WV shown in Figure 10a is more even than that in Figure 10b, which is near the ideal WV distribution in the vertical direction. Zhang et al [24] stated that the WV with an even distribution is beneficial for good tomography results obtained by the GNSS-WV tomography. Hence, at the epoch in Figure 10a, the WV profiles obtained by the two tomography methods were in good agreement with that obtained by the RS-Method.…”
Section: Tomography Results For the Comparison Between Methods 1 Andmentioning
confidence: 99%
“…The tomographic window has reached widespread applications in previous studies [24][25][26]. This "window" is based on the assumption that the WV of interest remains stationary across a period, and the length of the period determines the size of the window.…”
Section: General Tomographic Window and Existing Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the latter is obtained by subtracting the ZHD from ZTD. In our study, the observed multi-constellation GNSS data are processed using the multi-constellation GNSS Precise Point Positioning (PPP) software with precise orbit and clock error products (Zhao et al, 2018). Consequently, the SWD can be expressed as:…”
Section: Gnss Tropospheric Tomographymentioning
confidence: 99%
“…At this resolution, the inversion problem is ill-posed with several possible solutions. In the last decade, much effort has been applied to obtain a unique solution by adding additional constraints Mashhadi-Hossainali, 2014, 2015;Bender et al, 2011;Benevides et al, 2016;Flores et al, 2000;Gradinarsky and Jarlemark, 2004;Guo et al, 2016;Manning et al, 2012;Möller, 2017;Rohm, 2012b;Rohm and Bosy, 2009;Rohm et al, 2013;Troller, 2004a;Trzcina and Rohm, 2019;Xia et al, 2013;Zhao et al, 2018Zhao et al, , 2019. Flores et al (2000) applied horizontal constraints, vertical constraints and boundary conditions using the Singular Value Decomposition (SVD) to solve the tomography problem.…”
Section: Introductionmentioning
confidence: 99%